Asphalt-based hard carbon negative electrode material coated with ethylene tar-based asphalt and application of asphalt-based hard carbon negative electrode material

Through the asphalt-based hard carbon negative electrode material coated with ethylene tar-based asphalt, combined with acidification, modification and doping technology, a coating structure doped with hard carbon and soft carbon is formed, solving the problem of low conductivity in sodium ion batteries. , achieves high magnification and cycle performance, and expands the layer spacing.

CN119230759AInactive Publication Date: 2024-12-31ZHEJIANG CABORN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411708594.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sodium ion battery hard carbon anode materials have insufficient conductivity while ensuring a large layer spacing, resulting in low rate performance and poor cycle stability, and lack of measures to effectively improve the layer spacing.

Method used

The preparation method of asphalt-based hard carbon anode material coated with ethylene tar-based asphalt includes crushing, acidification, modification, doping carbonization, decomposition, melting, oxygen-through stirring, coating and secondary carbonization to form a hard carbon core and Soft carbon outer covering structure, increasing layer spacing and improving conductivity.

Benefits of technology

It achieves a higher first-time charging capacity and rate performance in sodium ion batteries, improves cycling performance, and ensures that the layer spacing reaches 0.38nm and above.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230759A_ABST
    Figure CN119230759A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion battery negative electrode materials, and particularly relates to an asphalt-based hard carbon negative electrode material coated with ethylene tar-based asphalt and application of the asphalt-based hard carbon negative electrode material. The invention provides an asphalt-based hard carbon negative electrode material coated with ethylene tar-based asphalt, and a preparation method of the asphalt-based hard carbon negative electrode material sequentially comprises the following steps: crushing, acidifying, modifying, doping and carbonizing, removing impurities, melting, introducing oxygen and stirring, coating, and secondarily carbonizing, so that 1, the interlayer spacing of the asphalt-based hard carbon negative electrode material coated with ethylene tar-based asphalt is at least 0.38 nm, and the thickness of the asphalt-based hard carbon negative electrode material coated with ethylene tar-based asphalt is at least 10 microns; the performance of the sodium-ion battery is high, namely, the first charge capacity and the first effect are high; 2, the material has outstanding conductivity, which is shown in sodium ion battery performance, namely relatively high rate capability and cycle performance;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode materials for sodium ion batteries, and in particular relates to an ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material and an application thereof. Background Art

[0002] Compared with the more common lithium-ion batteries, the main advantage of sodium-ion batteries is that they have a huge sodium reserve, which can greatly reduce the production cost of sodium-ion batteries. Correspondingly, lithium-ion batteries have also encountered a series of development bottlenecks such as specific capacity limit and scarce lithium resources. Therefore, the research on sodium-ion batteries, especially the research on negative electrode materials of sodium-ion batteries, has become increasingly important.

[0003] On the other hand, compared with soft carbon negative electrode materials, the advantage of hard carbon negative electrode materials is that the interlayer spacing of hard carbon is relatively large, which can reach 0.38nm, while the radius of sodium ions is 0.102nm, which can meet the reversible embedding and extraction of sodium ions. However, the former also has a disadvantage that cannot be ignored, that is, low conductivity, which is reflected in the performance of sodium ion batteries, that is, low rate performance and poor cycle stability under high current density.

[0004] Therefore, one of the important research directions of hard carbon negative electrode materials for sodium ion batteries is how to maximize their electrical conductivity, that is, their conductive performance, while at least maintaining the existing large interlayer spacing.

[0005] In addition, ethylene tar-based asphalt refers to a synthetic asphalt whose raw material composition mainly includes ethylene tar. Ethylene tar refers to a by-product obtained when hydrocarbons are cracked to produce ethylene, and its main use is to produce carbon black and be used as fuel for industrial boilers.

[0006] For example, the Chinese invention patent application with application publication number CN117756084A and application publication date 2024.03.26 discloses a method for preparing a hard carbon negative electrode material, comprising the following steps: The biomass powder is cleaned and dried, and then calcined and carbonized to obtain carbonized biomass powder; Mixing urea, pure water and the carbonized biomass powder, evaporating and removing the pure water after ultrasonic treatment to obtain a mixture of urea and the carbonized biomass powder; The mixture is ground, then calcined under an inert gas atmosphere, and then the calcined product is ball-milled to obtain a ball-milled product; The ball milled product is subjected to alkali washing, acid washing, drying and sieving to obtain a hard carbon negative electrode material.

[0007] The hard carbon negative electrode material in this invention patent application has an increased interlayer spacing, which improves the sodium storage performance of the hard carbon material and increases the reversible capacity, coulomb efficiency and cycle performance of the hard carbon material.

[0008] However, the hard carbon negative electrode material still has at least the following two shortcomings in actual use, which are also the technical problems to be solved by the present invention, namely: First, in the above preparation method, there is only a measure to increase the interlayer spacing, and there is no step to improve the conductivity. Therefore, the hard carbon negative electrode material only has a relatively large reversible capacity, and cannot achieve relatively strong rate performance and cycle stability. Second, even in terms of increasing the interlayer spacing, the above preparation method lacks sufficient measures and methods, including only adding a nitrogen source, namely N doping, which is far from enough. Ultimately, it is difficult to achieve the superiority of 0.38nm or even a larger interlayer spacing in the interlayer spacing data.

[0009] So to sum up, there is an urgent need for a hard carbon negative electrode material that has both greatly improved conductivity and significantly increased interlayer spacing. Summary of the invention

[0010] The present invention provides an ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material, and the preparation method thereof comprises the following steps in sequence: crushing, acidification, modification, doping carbonization, impurity removal, melting, oxygen stirring, coating, and secondary carbonization, so that: 1. The asphalt-based hard carbon negative electrode material coated with ethylene tar-based asphalt has an interlayer spacing of at least 0.38 nm, which is reflected in the performance of sodium ion batteries as a higher first charge capacity and first efficiency; 2. The material has outstanding conductive properties, which is reflected in the performance of sodium ion batteries as a higher rate performance and cycle performance.

[0011] On the other hand, the present invention also discloses an application of the above material, which can be used as a negative electrode material for sodium ion batteries and potassium ion batteries.

[0012] The technical solution adopted by the present invention to solve the above problem is: an ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material, the preparation method of which comprises the following steps in sequence: S1. Crushing: crushing ethylene tar to obtain asphalt powder; S2, acidification: adding the asphalt powder to concentrated nitric acid, stirring, washing, and finally drying to obtain acidified asphalt; S3, modification: firstly heating the acidified asphalt, then adding a modifier, and finally stirring and mixing to obtain modified asphalt; S4, doping carbonization: firstly adding the modified asphalt and urea into a graphite sagger, and then performing a heating operation to obtain a carbonized material; S5, impurity removal: grinding, stirring, pickling, filtering and drying the carbonized material in sequence to obtain a pitch-based hard carbon negative electrode material; S6, melting: taking ethylene tar-based asphalt separately, heating it under inert gas to obtain a molten material; S7, oxygen-passing and stirring: passing oxygen into the molten material, stirring under a slightly positive pressure, and finally cooling to obtain a coating material; S8, coating: adding the asphalt-based hard carbon negative electrode material and the coating material into a VC mixer, and performing a coating operation to obtain a coated body; S9, secondary carbonization: placing the coated body into a carbonization furnace and performing a carbonization operation to obtain a final ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material.

[0013] In the present invention, since ethylene tar is a carbon material rich in a large amount of condensed aromatic hydrocarbon molecular structures, if it is directly carbonized without being treated, it is easy to be graphitized, and then form a highly ordered carbon layer structure to form soft carbon.

[0014] Soft carbon materials are different from hard carbon materials. They have a more regular crystal structure and a smaller interlayer distance, which makes it difficult for sodium ions to embed into the gaps in the carbon layer structure, reducing its sodium storage capacity. In order to suppress the degree of asphalt graphitization during the carbonization process, a large number of functional groups such as carboxyl and hydroxyl groups can be introduced between the graphite layers through the above-mentioned acidification step. These functional groups and asphalt molecules produce cross-linking effects to form a three-dimensional cross-linked structure. Therefore, the microstructure of the carbonized graphite can be made more disordered, increasing the spacing between the graphite layers, and finally forming a coating structure of soft carbon and hard carbon doped with each other, which increases the conductivity while having the good sodium storage performance of hard carbon materials.

[0015] A further preferred technical solution is: S2. During the acidification, the mass fraction of concentrated nitric acid is 40-60%, and 1g of asphalt powder corresponds to 20-30ml of concentrated nitric acid.

[0016] A further preferred technical solution is that: in S3, in the modification, the modifier is any one or a mixture of several of calcium oxide, iron oxide, magnesium oxide and zinc oxide, and the weight ratio of the acidified asphalt to the modifier is 1:1.

[0017] In the present invention, the above-mentioned modifier can decompose to produce carbon oxide gas during the heating process, thereby consuming excess hydrogen and promoting the solid-phase pyrolysis of asphalt. This process can also hinder the formation of an ordered microcrystalline carbon structure.

[0018] A further preferred technical solution is that: in S4, during the doping carbonization, the weight ratio of the modified asphalt to urea is (1-5):1, and the carbonization temperature is 1300-1400°C.

[0019] In the present invention, urea is doped with N element. Through the conjugated structure doping of N atoms, the carbon material can be induced to produce structural defects and change the electronic state, effectively improving its surface properties, enhancing its wettability with the electrolyte, and providing more adsorption sites for the reversible binding of Na+.

[0020] A further preferred technical solution is that: in S5, during the impurity removal, the pickling operation is performed using 1 mol / L hydrochloric acid.

[0021] A further preferred technical solution is that: in S6, during melting, the temperature of the heating operation is 150-350°C.

[0022] A further preferred technical solution is that: S7, during the oxygen stirring, the pressure value of the slight positive pressure is 50-400Pa higher than the atmospheric pressure.

[0023] A further preferred technical solution is that: in S8, during coating, the weight of the coating material is 5-20% of the weight of the asphalt-based hard carbon negative electrode material.

[0024] A further preferred technical solution is: S9, in the secondary carbonization, the carbonization temperature is 1100-1300°C, the heating rate is 2-5°C / min, and the carbonization time is 2-6h.

[0025] In the present invention, the coating is carbonized again at low temperature on the surface of the asphalt-based hard carbon negative electrode material, so that the coating layer structure is a mixture of soft carbon and hard carbon, which can improve the sodium storage capacity of the final negative electrode material and its conductivity.

[0026] In other words, the final ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material has a structure consisting of a hard carbon inner core and an outer coating of a combination of soft carbon and hard carbon.

[0027] An application of an ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material, wherein the ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material is used as a negative electrode material for sodium ion batteries and potassium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a step diagram of the preparation method in the present invention.

[0029] Figure 2 This is a microstructure photograph of the final coated negative electrode material in Example 1 of the present invention.

[0030] Figure 3 This is a microstructure photograph of the final coated negative electrode material in Example 2 of the present invention.

[0031] Figure 4This is a microstructure photograph of the final coated negative electrode material in Example 3 of the present invention.

[0032] Figure 5 This is a microstructure photograph of the uncoated asphalt-based hard carbon negative electrode material in Comparative Example 1 of the present invention.

[0033] Figure 6 This is a microstructure photograph of the final coated negative electrode material in Comparative Example 2 of the present invention.

[0034] Figure 7 This is a microstructure photograph of the final coated negative electrode material in Comparative Example 3 of the present invention.

[0035] Figure 8 The figures are the performance test results of negative electrode materials and sodium ion batteries in three embodiments and three comparative examples of the present invention. DETAILED DESCRIPTION

[0036] The following descriptions are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention.

[0037] Example 1 As attached Figure 1 , 2 As shown, an ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material, the preparation method of which comprises the following steps in sequence: 1. First, crush 2g of ethylene tar into powder, then add the asphalt powder into 50mL of 50% concentrated nitric acid, stir continuously for 12 hours, wash repeatedly with deionized water, and finally dry in an oven at 65℃ to obtain acidified asphalt; 2. Select zinc oxide as the modifier, heat the acidified asphalt to 350°C and mix it with the modifier in a ratio of 1:1 to prepare modified asphalt; 3. Pour the modified asphalt and urea into a graphite sagger in a ratio of 1:1, heat to 1400°C, and carbonize for 3 hours to obtain carbonized material; 4. Take out the carbonized material, grind it into powder with a mortar, add an appropriate amount of 1M hydrochloric acid to soak it, and stir it magnetically for 5 hours to remove impurities to obtain a pitch-based hard carbon negative electrode material; 5. Heat the ethylene tar-based asphalt to 200°C under inert gas to preheat and melt, introduce oxygen under slight positive pressure and stir to react for 4 hours, and obtain the coating material after cooling; 6. Take 5wt% of the coating material and asphalt-based hard carbon negative electrode material and add them to the VC mixer. After coating for 35 minutes, put it into the carbonization furnace and heat it to 1200℃ at a heating rate of 2℃ / min. Carbonize at 1200℃ for 3h to obtain the final ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material.

[0038] Example 2 As attached Figure 1 , 3 As shown, an ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material, the preparation method of which comprises the following steps in sequence: 1. First, crush 2g of ethylene tar into powder, then add the asphalt powder into 50mL of 40% concentrated nitric acid, stir continuously for 18 hours, wash repeatedly with deionized water, and finally dry in an oven at 65℃ to obtain acidified asphalt; 2. Calcium oxide is selected as a modifier, and the acidified asphalt is heated to 350°C and mixed with the modifier in a ratio of 1:1 to prepare modified asphalt; 3. Pour the modified asphalt and urea into a graphite sagger at a ratio of 2:1, heat to 1350°C, and carbonize for 4 hours to obtain carbonized material; 4. Take out the carbonized material, grind it into powder with a mortar, add an appropriate amount of 1M hydrochloric acid to soak it, and stir it magnetically for 5 hours to remove impurities to obtain a pitch-based hard carbon negative electrode material; 5. Heat the ethylene tar-based asphalt to 250°C under inert gas to preheat and melt, introduce oxygen at a slightly positive pressure and stir to react for 5 hours, and obtain the coating material after cooling; 6. Take 10wt% of the coating material and asphalt-based hard carbon negative electrode material and add them to the VC mixer. After coating for 40 minutes, put it into the carbonization furnace and heat it to 1100℃ at a heating rate of 3℃ / min. Carbonize at 1100℃ for 5 hours to obtain the final ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material.

[0039] Example 3 As attached Figure 1 , 4 As shown, an ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material, the preparation method of which comprises the following steps in sequence: 1. First, crush 2g of ethylene tar into powder, then add the asphalt powder into 50mL of 60% concentrated nitric acid, stir continuously for 24 hours, wash repeatedly with deionized water, and finally dry in an oven at 65℃ to obtain acidified asphalt; 2. Select magnesium oxide as the modifier, heat the acidified asphalt to 350°C and mix it with the modifier in a ratio of 1:1 to prepare modified asphalt; 3. Pour the modified asphalt and urea into a graphite sagger at a ratio of 3:1, heat to 1400°C, and carbonize for 5 hours to obtain carbonized material; 4. Take out the carbonized material, grind it into powder with a mortar, add an appropriate amount of 1M hydrochloric acid to soak it, and stir it magnetically for 5 hours to remove impurities to obtain a pitch-based hard carbon negative electrode material; 5. Heat the ethylene tar-based asphalt to 300°C under inert gas to preheat and melt, introduce oxygen under slight positive pressure and stir to react for 8 hours, and obtain the coating material after cooling; 6. Take 15wt% of the coating material and asphalt-based hard carbon negative electrode material and add them to the VC mixer. After coating for 50 minutes, put it into the carbonization furnace and heat it to 1250℃ at a heating rate of 5℃ / min. Carbonize at 1250℃ for 6h to obtain the final ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material.

[0040] Comparative Example 1 As attached Figure 1 , 5 As shown, a pitch-based hard carbon negative electrode material, the preparation method of which comprises the following steps in sequence: 1. First, crush 2g of ethylene tar into powder, then add the asphalt powder into 50mL of 50% concentrated nitric acid, stir continuously for 12 hours, wash repeatedly with deionized water, and finally dry in an oven at 65℃ to obtain acidified asphalt; 2. Select zinc oxide as the modifier, heat the acidified asphalt to 350°C and mix it with the modifier in a ratio of 1:1 to prepare modified asphalt; 3. Pour the modified asphalt and urea into a graphite sagger in a ratio of 1:1, heat to 1400°C, and carbonize for 3 hours to obtain carbonized material; 4. Take out the carbonized material, grind it into powder with a mortar, add an appropriate amount of 1M hydrochloric acid to soak it, and stir it magnetically for 5 hours to remove impurities to obtain a pitch-based hard carbon negative electrode material.

[0041] Comparative Example 2 As attached Figure 1 , 6 As shown, an ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material, the preparation method of which comprises the following steps in sequence: 1. First, crush 2g of ethylene tar into powder, then add the asphalt powder into 50mL of 50% concentrated nitric acid, stir continuously for 12 hours, wash repeatedly with deionized water, and finally dry in an oven at 65℃ to obtain acidified asphalt; 2. Select zinc oxide as the modifier, heat the acidified asphalt to 350°C and mix it with the modifier in a ratio of 1:1 to prepare modified asphalt; 3. Pour the modified asphalt and urea into a graphite sagger in a ratio of 1:1, heat to 1400°C, and carbonize for 3 hours to obtain carbonized material; 4. Take out the carbonized material, grind it into powder with a mortar, add an appropriate amount of 1M hydrochloric acid to soak it, and stir it magnetically for 5 hours to remove impurities to obtain a pitch-based hard carbon negative electrode material; 5. Heat the ethylene tar-based asphalt to 140°C under inert gas to preheat and melt, introduce oxygen under slight positive pressure and stir to react for 4 hours, and obtain the coating material after cooling; 6. Take 5wt% of the coating material and asphalt-based hard carbon negative electrode material and add them to the VC mixer. After coating for 35 minutes, put it into the carbonization furnace and heat it to 1200℃ at a heating rate of 2℃ / min. Carbonize at 1200℃ for 3h to obtain the final ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material.

[0042] Comparative Example 3 As attached Figure 1 , 7 As shown, an ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material, the preparation method of which comprises the following steps in sequence: 1. First, crush 2g of ethylene tar into powder, then add the asphalt powder into 50mL of 50% concentrated nitric acid, stir continuously for 12 hours, wash repeatedly with deionized water, and finally dry in an oven at 65℃ to obtain acidified asphalt; 2. Select zinc oxide as the modifier, heat the acidified asphalt to 350°C and mix it with the modifier in a ratio of 1:1 to prepare modified asphalt; 3. Pour the modified asphalt and urea into a graphite sagger in a ratio of 1:1, heat to 1400°C, and carbonize for 3 hours to obtain carbonized material; 4. Take out the carbonized material, grind it into powder with a mortar, add an appropriate amount of 1M hydrochloric acid to soak it, and stir it magnetically for 5 hours to remove impurities to obtain a pitch-based hard carbon negative electrode material; 5. Heat the ethylene tar-based asphalt to 200°C under inert gas to preheat and melt, introduce oxygen under slight positive pressure and stir to react for 4 hours, and obtain the coating material after cooling; 6. Take 30wt% of the coating material and asphalt-based hard carbon negative electrode material and add them to the VC mixer. After coating for 35 minutes, put it into the carbonization furnace and heat it to 1200℃ at a heating rate of 2℃ / min. Carbonize at 1200℃ for 3h to obtain the final ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material.

[0043] Performance Testing 1. Active material SP: CMC: SBR = 94: 1.5: 3, prepare slurry with deionized water, place the slurry in a degassing machine, stir at 800rpm for 10min; then stir at 2000rpm for 20min, check the flow of the liquid after stopping; scoop the slurry onto the copper foil that has been wiped clean (with alcohol), adjust the scraper thickness to 150um, and start the coater; place the copper foil after coating in a vacuum oven, dry it at 100℃ for 2h, and then use 80℃ vacuum drying for 8h; place the dried pole piece in a roller press for rolling, adjust the gap at both ends to 30um, and roll it, and record the thickness of the pole piece before and after rolling; punch the pole piece into an electrode with a diameter of 14.00mm on a manual punching machine dedicated to button batteries; weigh more than 6 pole pieces of similar mass, and record the weight of the pole piece and the current collector; bake the pole piece in a vacuum oven at 120℃ for 4h, then take it out and quickly put it in the glove box.

[0044] 2. Bring the negative electrode sheet into the glove box and assemble it in the order of sodium sheet and diaphragm negative electrode. Use 80-150 μL of electrolyte specially designed for sodium battery to drip. Use insulated tweezers to place the button battery with the negative electrode side facing up on the button battery sealing machine mold. Adjust the pressure (generally more than 800 kg). Take it out with insulated tweezers, observe whether the appearance of the preparation is complete and wipe it clean with dust-free paper.

[0045] 3. After taking out, conduct cycle performance test: a. Let stand for 10 hours; b. Constant current discharge (0.1C) to 0.005V; c. Constant voltage discharge (0V) with cut-off current 0.02mA; d. Let stand for 5min; e. Constant current charge (0.1C) to 1.5V; f. Let stand for 5min; g. Start from step b and cycle for more than 100 times.

[0046] 4. Perform rate performance test after taking out: a. Let stand for 10 hours; b. Constant current discharge (0.1C) to 0.005V; c. Constant voltage discharge (0V) with cut-off current 0.02mA; d. Let stand for 5min; e. Constant current charge (0.1C) to 1.5V; f. Let stand for 5min; g. Start from step b and give 0.5C for rate performance test.

[0047] The final performance test results are attached. Figure 8 Analysis Summary The final negative electrode materials in the first and third embodiments all have the dual advantages of large interlayer spacing and high conductivity, which is manifested in high rate performance and cycle performance in sodium ion batteries; Second, the negative electrode material in Comparative Example 1 lacks the coating step required in the embodiment. The negative electrode material in Comparative Example 2 has the problem of incomplete melting of the ethylene tar-based asphalt used for coating. The negative electrode material in Comparative Example 3 has an excessively high content of the ethylene tar-based asphalt used for coating. Figure 8 The performance test results show that the interlayer spacing is small and the electrical conductivity is low, which also proves the necessity of the above-mentioned limiting conditions from the opposite side.

[0048] Third, the interlayer spacing of the negative electrode materials in the three comparative examples cannot reach ≥ 0.38 nm, which also shows that the above-mentioned limiting conditions, at the level of negative electrode materials, also have the effect of expanding the interlayer spacing or maintaining a larger interlayer spacing.

[0049] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various modifications can be made within the knowledge of ordinary technicians in the technical field without departing from the purpose of the present invention. These are all non-creative modifications and are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. An ethylene tar-based asphalt-coated hard carbon negative electrode material, characterized in that The preparation method comprises the following steps in sequence: S1. Crushing: crushing ethylene tar to obtain asphalt powder; S2, acidification: adding the asphalt powder to concentrated nitric acid, stirring, washing, and finally drying to obtain acidified asphalt; S3, modification: firstly heating the acidified asphalt, then adding a modifier, and finally stirring and mixing to obtain modified asphalt; S4, doping carbonization: firstly adding the modified asphalt and urea into a graphite sagger, and then performing a heating operation to obtain a carbonized material; S5, impurity removal: grinding, stirring, pickling, filtering and drying the carbonized material in sequence to obtain a pitch-based hard carbon negative electrode material; S6, melting: taking ethylene tar-based asphalt separately, heating it under inert gas to obtain a molten material; S7, oxygen-passing and stirring: passing oxygen into the molten material, stirring under a slightly positive pressure, and finally cooling to obtain a coating material; S8, coating: adding the asphalt-based hard carbon negative electrode material and the coating material into a VC mixer, and performing a coating operation to obtain a coated body; S9, secondary carbonization: placing the coated body into a carbonization furnace and performing a carbonization operation to obtain a final ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material.

2. The ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: S2. During acidification, the mass fraction of concentrated nitric acid is 40-60%, and 1g of asphalt powder corresponds to 20-30ml of concentrated nitric acid.

3. The ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: S3. In the modification, the modifier is any one or a mixture of several of calcium oxide, iron oxide, magnesium oxide and zinc oxide, and the weight ratio of the acidified asphalt to the modifier is 1:

1.

4. The ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: S4. In the doping carbonization, the weight ratio of the modified asphalt and urea is (1-5):1, and the carbonization temperature is 1300-1400°C.

5. The ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: S5. During the impurity removal, the pickling operation is carried out using 1 mol / L hydrochloric acid.

6. The ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: S6. During melting, the heating operation temperature is 150-350°C.

7. The ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: S7. During oxygen stirring, the slightly positive pressure is 50-400Pa higher than the atmospheric pressure.

8. The ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: S8. During the coating, the weight of the coating material is 5-20% of the weight of the asphalt-based hard carbon negative electrode material.

9. The ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: S9. In the secondary carbonization, the carbonization temperature is 1100-1300°C, the heating rate is 2-5°C / min, and the carbonization time is 2-6h.

10. An application of the asphalt-based hard carbon negative electrode material coated with ethylene tar-based asphalt as claimed in any one of claims 1 to 9, characterized in that: The ethylene tar-based asphalt-coated asphalt-based hard carbon negative electrode material is used as a negative electrode material for sodium ion batteries and potassium ion batteries.

Citation Information

Patent Citations

  • Preparation method of hard carbon negative electrode material, negative electrode plate and sodium ion battery

    CN117756084A

  • Asphalt-based sodium ion battery negative electrode material and preparation method thereof

    CN116002662A

  • Negative electrode material and preparation method thereof, negative electrode plate, battery cell and sodium ion battery

    CN116715219A

  • Asphalt-based hard carbon negative electrode material and preparation method and application thereof

    CN116936800A

  • Preparation method and application of high-performance sodium ion battery hard carbon negative electrode material

    CN117352652A

Cited By

  • Preparation method of asphalt-based hard carbon material

    CN122212095A